Leaning into the Crisis: Managing COVID-19 in Social Services and Behavioral Health Agencies. Issue 4 (8th August 2021) - Neely-Barnes, Susan; Hunter, Anna; Meiman, Julie; Malone, Cherry; Hirschi, Melissa; Delavega, Elena
ABSTRACT: In early 2020, the COVID-19 pandemic hit the United States causing significant disruptions in daily life including disruptions for social service and behavioral health agencies. This qualitative, phenomenological study interviewed thirty-seven directors or managers of social service or behavioral health agencies. Agency managers described challenges related to the pandemic and shut down, but they also described opportunities for innovation and change. Agency managers discussion fell into eight themes: funding, employees, space, supplies, policies/protocols, partnerships, mission, and innovation/leaning into the crisis. Implications for administrative practice and policy will be discussed.